An exotic plant successfully invaded as a passenger driven by light availability - Liu, Yanyan; Li, Wenjun; Sui, Xiaolin; Li, Airong; Li, Kaihui; Gong, Yanming (Frontiers in Plant Science, 2022)
Invasive exotic plant species (IEPs) are widely distributed across the globe, but whether IEPs are drivers or passengers of habitat change in the invaded spaces remains unclear. Here, we carried out a vegetation and soil survey in 2018 and two independent field experiments (Pedicularis kansuensis removal in 2014 and 2015, and fertilization experiment since 2012) and found that the invasive annual P. kansuensis was at a disadvantage in light competition compared with perennial native grasses, but the successful invasion of P. kansuensis was due to the sufficient light resources provided by the reduced coverage of the native species. Conversely, nitrogen enrichment can effectively inhibit P. kansuensis invasion by increasing the photocompetitive advantage of the native species. sP. kansuensis invasion did not reduce species richness, but did increase plant community coverage, productivity and soil nutrients. Furthermore, the removal of P. kansuensis had little effect on the plant community structure and soil properties. Our results suggest that the passenger model perfectly explains the benign invasive mechanism of P. kansuensis. The invasion “ticket” of P. kansuensis is a spare ecological niche for light resources released by overgrazing.